The Effect of Hedonic Shopping Motivation and Shopping Lifestyle on Impulsive Buying - Hanafiah, S; Soegoto, H (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This study was conducted with the aim of knowing the effect between hedonic shopping motivation and shopping lifestyle on impulsive buying of Tokopedia consumers. The method used in this research is quantitative, which is a study that aims to explain an empirical phenomenon accompanied by statistical data, characteristics and relationships between variables using techniques data collection using questionnaires. Data collection in this study was carried out by distributing questionnaires using a Likert scale. The sample in this study was the International Women University Bandung students who are Tokopedia consumers. The data analysis technique in this study is multiple linear regression with SPSS tools to determine the effect simultaneously and partially. The results of this study are hedonic shopping motivation and shopping lifestyle have a positive and significant effect on impulsive buying simultaneously. Partially, hedonic shopping motivation variables have a positive and significant effect on impulsive buying, while shopping lifestyle partially has no positive and significant effect on impulsive buying. The impact of this study is to provide an overview of how impulsive buying can occur due to hedonic shopping motivation and shopping lifestyle.